Does paternity leave matter for female employment in developing economies? Evidence from firm-level data. Issue 16 (1st November 2016) - Amin, Mohammad; Islam, Asif; Sakhonchik, Alena
ABSTRACT: Analysis using firm-level data for a sample of 33, 302 firms in 53 developing countries shows that women's employment among private firms is significantly higher in countries that mandate paternity leave versus those that do not. A conservative estimate suggests an increase of 6.8 percentage points in the proportion of women workers associated with mandating paternity leave. The empirical specification is immune to spurious correlations that affect the level of women and men employment equally and also robust to a large number of controls for country and firm characteristics.